Hubungan Pengetahuan Aplikasi Digital Dalam Membantu Proses Pelayanan Di PT. Pegadaian Kantor Cabang Waitabula - Karolus W. Rato; Nixon Malo; Maria N. Lende; Susanti Ngara; Antonius B.Dairo (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Pegadaian is a State-Owned Enterprise (BUMN) in Indonesia which officially has permission to carry out financial institution activities in the form of financing in the form of channeling credit funds to the public on the basis of pawn law. PT Pegadaian is a form of non-bank financial institution which has activities to finance community needs, both productive and consumptive. Objective: To find out the implementation of PT pawning. Pawnshop